Development of a dose verification system for Vero4DRT using Monte Carlo method. (8th November 2014) - Ishihara, Yoshitomo; Sawada, Akira; Nakamura, Mitsuhiro; Miyabe, Yuki; Tanabe, Hiroaki; Kaneko, Shuji; Takayama, Kenji; Mizowaki, Takashi; Kokubo, Masaki; Hiraoka, Masahiro
Abstract : Vero4DRT is an innovative image‐guided radiotherapy system employing a C‐band X‐ray head with gimbal mechanics. The purposes of this study were to propose specific MC models of the linac head and multileaf collimator (MLC) for the Vero4DRT and to verify their accuracy. For a 6 MV photon beam delivered by the Vero4DRT, a simulation code was implemented using EGSnrc. The linac head model and the MLC model were simulated based on its specification. Next, the percent depth dose (PDD) and beam profiles at depths of 15, 100, and 200 mm were simulated under source‐to‐surface distance of 900 and 1000 mm. Field size was set to 150 × 150 mm 2 at a depth of 100 mm. Each of the simulated dosimetric metrics was then compared with the corresponding measurements by a 0.125 cc ionization chamber. After that, intra‐ and interleaf leakage, tongue‐and‐groove, and rounded‐leaf profiles were simulated for the static MLC model. Meanwhile, film measurements were performed using EDR2 films under similar conditions to simulation. The measurement for the rounded‐leaf profile was performed using the water phantom and the ionization chamber. The leaf physical density and abutting leaf gap were adjusted to obtain good agreement between the simulated intra‐ and interleaf leakage profiles and measurements. For the MLC model in step‐and‐shoot cases, a pyramid and a prostate IMRT field were simulated, while film measurements were performed using EDR2. For the linac head, exclusive of MLC, the difference in PDD was < 1.0 % after the buildup region. The simulated beam profiles agreed to within 1.3% at each depth. The MLC model has been shown to reproduce dose measurements within 2.5% for static tests. The MLC is made of tungsten alloy with a purity of 95%. The leaf gap of 0.015 cm and the MLC physical density of 18.0 g / cm 3, which provided the best agreement between the simulated and measured leaf leakage, were assigned to our MC model. As a result, the simulated step‐and‐shoot IMRT dose distributions agreed with the film measurements to within 3.3%, with exception of the penumbra region. We have developed specific MC models of the linac head and the MLC in the Vero4DRT system. The results have demonstrated that our MC models have high accuracy. PACS numbers: 87.55.K‐, 87.56.nk, 87.56.bd